2007
DOI: 10.1093/ndt/gfl714
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular acidosis after kidney transplantation--incidence, risk factors and clinical implications

Abstract: Although long-term kidney recipients have a relatively high prevalence of RTA, it is usually mild and subclinical. Further studies are needed to clarify long-term effects of RTA in kidney recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 23 publications
3
54
3
1
Order By: Relevance
“…Type 1 classic distal RTA has been reported more frequently in kidney recipients. 2,3,5,[8][9][10] Similarly, in this study, we observed that the presence of distal RTA was higher compared with other types of RTA.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Type 1 classic distal RTA has been reported more frequently in kidney recipients. 2,3,5,[8][9][10] Similarly, in this study, we observed that the presence of distal RTA was higher compared with other types of RTA.…”
Section: Discussionsupporting
confidence: 77%
“…1 Particularly, in the early posttransplant period, it is frequent because of acute rejection, suboptimal allograft function, calcineurin inhibitor (CNI) nephrotoxicity, and ischemic tubular dysfunction. 2 Type 2 (proximal) RTA, the common form of RTA, is characterized by the decrement of bicarbonate reabsorption in proximal tubule because of the toxic effects of CNIs or persisting hyperparathyroidism. RTA might completely improve during the first 6 months after transplantation because tubular damage and hyperparathyroidism resolves.…”
Section: Introductionmentioning
confidence: 99%
“…The use of tacrolimus is often limited by many side effects such as tremor, hemolytic-uremic syndrome, arterial hypertension, hyperlipidemia, and a higher incidence of new-onset diabetes mellitus. Despite these adverse side effects, FK506 can also be nephrotoxic, causing reduced glomerular filtration rate (GFR) and distal renal tubular acidosis (dRTA), which are strongly restrictive for continuing the drug (21,37,39).Several studies in renal organ transplant patients have observed a significant correlation between dRTA and tacrolimus treatment (22,27,44). In addition, the prevalence of RTA in renal transplant recipients with a functioning graft has been associated with treatment with calcineurin inhibitors such as FK506 (22, 44).…”
mentioning
confidence: 99%
“…Several studies in renal organ transplant patients have observed a significant correlation between dRTA and tacrolimus treatment (22,27,44). In addition, the prevalence of RTA in renal transplant recipients with a functioning graft has been associated with treatment with calcineurin inhibitors such as FK506 (22, 44).…”
mentioning
confidence: 99%
“…Type IV RTA can also been seen in patients with a renal transplant (225). This could be due to either an immune mediated mechanism or it could be related to medications used for the treatment of rejection.…”
Section: Acquiredmentioning
confidence: 99%